TASAWUF ENTERPRENEURSHIP: MEMBANGUN ETIKA KEWIRAUSAHAAN BERBASIS PROPHETIC INTELLIGENCE - Shobir, Labib Muzaki (UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
Sufism should not be implied to the activity oriented to activities away fromthe world. Sufism should be used as a spirit to ever y Muslim to accumulatewealth in the world. However, the world’s wealth is eventually used to struggleto collect charity for the hereafter. Prophetic Intelligence is the study of mysticismthat can be used to integrate the interests of the world and the hereafter. Thepractice of prophetic intelligence is referring to the example of the ProphetMohammad SAW. One side as the Prophet, He expands the task of forhereafter issues. In the other side as a trader, he exemplifies efforts to becomeentrepreneurs in the world. The example of the Prophet Muhammad is anexample of ethical entrepreneurship. Tasawuf tidak seharusnya diimplikasikan kepada aktivitas yang berorientasikepada kegiatan yang menjauhi dunia. Tasawuf harus digunakan sebagaispirit bagi setiap Muslim untuk mengumpulkan kekayaan di dunia. Namun, kekayaan dunia tersebut pada akhirnya digunakan untuk berjuang mengumpulkan amal akhirat. Prophetic Intelligence merupakansalah kajian tasawuf yang bisa digunakan untuk memadukan kepentingandunia dan akhirat. Praktek tasawuf prophetic intelligence adalah mengacu kepada teladan Nabi Muhamamd SAW. Satu sisi sebagai Rasulullahyang mengembang tugas akhirat. Sisi lain adalah sebagai pedagang yangmencontohkan usaha menjadi wirausahawan di dunia. Teladan NabiMuhammad SAW tersebut merupakan contoh etika kewirausahaan.